Моделі синхронізації безконфліктних реплікованих типів даних в мобільних офлайн застосунках - Полторацький, А. О. (ХНУРЕ, 2020)
There are a lot of ad-hoc and error-prone approaches for eventual consistency. This article reviews the solution of the problem of data synchronization in offline applications. The main goal is to describe main models and approaches of synchronization using existing conflict-free replicated data types (CRDTs). It describes main principles of CmRDT, CvRDT and their modifications. CRDT will be compared to Operational Transformation in scope of text editing tasks. Finally, we will make a conclusion about feasibility of implementation of CRDTs in mobile applications